Could the understanding of the strawberry softening process benefit from aquaporins? - Alleva, Karina Edith (2011)
The Major Intrinsic Protein (MIP) family includes a main group of key channels known as aquaporins (AQPs), described for sharing a very conservative structure with a pore that facilitates water and/or solute permeation. Since its first member was functionally reported in 1992, AQPs were found to be abundantly expressed in all kingdoms. Although many roles have been attributed to these small integral proteins, it is becoming evident that the number and type of AQPs within a membrane are major determinants of its water transport capacity. Thus, their presence is opening new perspectives to understand the role of plant cell membrane water transport in physiological and developmental processes. Strawberry is a fleshy fruit characterized by a rapid loss of firmness during ripening, limiting the shelf-life of these fruit. Even though fruit texture is influenced by various factors like structural integrity of primary cell wall, sugar accumulation, and the turgor pressure generated within cells by osmosis, main attention has been focused on degradation of cell wall polysaccharides. Turgor pressure, in spite of long being mentioned as a possible player in softening during fruit development, has not received proper consideration. In the light of AQP outbreak, it is worth questioning how these channels could contribute to strawberry fruit softening. In an attempt to answer this question, this review summarizes the current available information on plant AQPs, extending the knowledge to those specifically expressed in fruits to finally discuss the recent reported findings in strawberry, particularly those associated with ripening and softening processes.